STUDI FENOMENOLOGI : BAGAIMANA SISWA MENJALANKAN PENDIDIKAN DAN LATIHAN DI KELAS X SMAN OLAHRAGA PROVINSI RIAU - Dian Mutiara Harsa; Muhammad Imam Rahmatullah; Sri Agustina Ratnawati; Aref Vai; Rola Angga Lardika; Purwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the experiences of tenth-grade students in balancing academic education and sports training at SMAN Olahraga Provinsi Riau. The research employed a qualitative phenomenological approach to explore students’ lived experiences as student-athletes. Data were collected through observation, interviews, documentation, and open-ended questionnaires involving 15 student-athletes from various sports branches. The findings revealed that students experienced dual-role demands as learners and athletes, requiring strong discipline, time management, and physical and mental readiness. Daily activities began at 05.00 a.m. and continued until night, including training sessions, classroom learning, dormitory activities, and independent study. The intensive schedule caused physical fatigue such as muscle pain, drowsiness, and decreased stamina, as well as mental fatigue including stress, boredom, reduced concentration, and declining learning motivation. These conditions affected both academic performance and sports achievement. However, students applied several coping strategies to maintain balance between education and training. The strategies included time management, maintaining healthy lifestyles, seeking social support from friends, teachers, coaches, and parents, as well as using religious approaches and self-motivation to reduce stress. The study concludes that student-athletes at sports schools face complex challenges in managing academic and athletic responsibilities simultaneously. Therefore, collaboration among schools, teachers, coaches, dormitory supervisors, and parents is necessary to create a supportive environment that promotes students’ academic success, athletic achievement, and mental well-being.